Radon exposure and tumors of the central nervous system - Alberto Ruano-Ravina; Ana Dacosta-Urbieta; Juan Miguel Barros-Dios; Karl T. Kelsey (Elsevier, 2018)
Objective: To review the published evidence of links between radon exposure and central nervous system tumors through a systematic review of the scientific literature. Methods: We performed a thorough bibliographic search in Medline (PubMed) and EMBASE. We combined MeSH (Medical Subject Heading) terms and free text. We developed a purpose-designed scale to assess the quality of the included manuscripts. Results: We have included 18 studies, 8 performed on miners, 3 on the general population and 7 on children, and the results have been structured using this classification. The results are inconclusive. An association between radon exposure and central nervous system tumors has been observed in some studies on miners, but not in others. The results observed in the general adult population and in children are also mixed, with some research evincing a statistically significant association and others showing no effect. Conclusions: We cannot conclude that there is a relationship between radon exposure and central nervous system tumors. The available studies are extremely heterogeneous in terms of design and populations studied. Further research is needed in this topic, particularly in the general population residing in areas with high levels of radon. Resumen: Objetivo: Revisar la evidencia publicada entre la exposición al radón y los tumores del sistema nervioso central a través de una revisión sistemática de la literatura científica. Método: Se realiza una revisión sistemática exhaustiva de la literatura científica en Medline (PubMed) y EMBASE, combinando términos MeSH (Medical Subject Heading) y texto libre. Se desarrolla una escala específica para valorar la calidad de los estudios incluidos. Resultados: Se incluyeron 18 estudios (8 realizados en mineros, 3 en población general y 7 en niños) y los resultados se estructuraron siguiendo esa clasificación. Los resultados son inciertos. Algunos estudios en mineros han observado una asociación entre la exposición a radón y tumores del sistema nervioso central, pero otros no. Los resultados en población general adulta y en niños también son diversos, con algunas investigaciones que encuentran una asociación estadísticamente significativa y otras que no encuentran ningún efecto. Conclusiones: No puede concluirse que exista una asociación entre la exposición al radón y los tumores del sistema nervioso central. Los estudios disponibles son muy heterogéneos en cuanto al diseño y los sujetos incluidos. Es necesaria más investigación sobre este tema, en particular en población general residente en áreas con elevados niveles de radón. Keywords: Central nervous system neoplasms, Radon, Systematic review, Palabras clave: Sistema nervioso central, Radón, Revisión sistemática